The effectiveness of high-intensity interval training on body composition, cardiorespiratory fitness, and cardiovascular risk factors in children: A protocol for a systematic review - Solera-Martínez, Montserrat (Medicine (Baltimore), 2020)
BACKGROUND: No previous systematic review has examined the effect of high-intensity interval training (HIIT) interventions on body composition, cardiometabolic risk factors and cardiorespiratory fitness (CRF) in healthy schoolchildren from 5 to 12 years old. METHODS: This study will be conducted by following the guideline of the preferred reporting items for systematic review and meta-analysis protocols. An electronic search in MEDLINE (via PubMed), EMBASE (via Scopus), SPORTDiscus, Cochrane Library and Web of Science databases of all dates from inception will be conducted. We will include randomized controlled trials aimed to assess the effectiveness of HIIT to improve cardiometabolic risk factors, body composition, and CRF in children. Two authors will perform the study selection and data collection; disagreements will be solved by a third reviewer. The methodological quality of studies will be assessed by the Cochrane Collaboration's tool for assessing risk of bias (RoB2). Data analysis and synthesis will be performed by Comprehensive Meta-analysis Software and StataSE software, version 15. CONCLUSION: The results should be disseminated through publication in a peer-reviewed journal. Since the data used in systematic reviews of this type will be extracted exclusively from published studies, approval form and ethics committee will not be required.